Double-Stranded RNA-Activated Protein Kinase (PKR) Is Negatively Regulated by 60S Ribosomal Subunit Protein L18 - Kumar, Kotlo U. (American Society for Microbiology, 1999)
The double-stranded RNA (dsRNA)-activated protein kinase (PKR) provides a fundamental control step in the regulation of protein synthesis initiation through phosphorylation of the alpha subunit of eukaryotic translation initiation factor 2 (eIF-2α), a process that prevents polypeptide chain initiation. In such a manner, activated PKR inhibits cell growth and induces apoptosis, whereas disruption of normal PKR signaling results in unregulated cell growth. Therefore, tight control of PKR activity is essential for regulated cell growth. PKR is activated by dsRNA binding to two conserved dsRNA binding domains within its amino terminus. We isolated a ribosomal protein L18 by interaction with PKR. L18 is a 22-kDa protein that is overexpressed in colorectal cancer tissue. L18 competed with dsRNA for binding to PKR, reversed dsRNA binding to PKR, and did not directly bind dsRNA. Mutation of K64E within the first dsRNA binding domain of PKR destroyed both dsRNA binding and L18 interaction, suggesting that the two interactive sites overlap. L18 inhibited both PKR autophosphorylation and PKR-mediated phosphorylation of eIF-2α in vitro. Overexpression of L18 by transient DNA transfection reduced eIF-2α phosphorylation and stimulated translation of a reporter gene in vivo. These results demonstrate that L18 is a novel regulator of PKR activity, and we propose that L18 prevents PKR activation by dsRNA while PKR is associated with the ribosome. Overexpression of L18 may promote protein synthesis and cell growth in certain cancerous tissue through inhibition of PKR activity.